Applying the Principle of Strict Liability in Environmental Protection: Ministry of Environment and Forestry of the Republic of Indonesia (KLHK RI) against PT Waimusi Agroindah - Wijaya, Ryan Hendrich Dharma (Ajudikasi : Jurnal Ilmu Hukum, 2024)
Forest and land fires are an unavoidable chore for Indonesia every year. Law enforcement continues to be pursued to hold the perpetrators responsible for the losses arising from the fires. This research analyses the validity of PT WMA's corporate position as a legal subject to be liable using the principle of strict liability for fires that occur in Indonesia. It also analyses the application of collateral confiscation in providing certainty over liability in accordance with the applicable verdict. This research is normative juridical in nature by analysing Decision Number 234/Pdt.G/LH.2016/PN.Plg by using several approaches, namely juridical approach, statutory approach and conceptual approach. Based on the results of the research, it is concluded that PT WMA is legally a legal subject that is absolutely responsible for the fires that occurred in its work area and the application of collateral confiscation can be carried out if this is confirmed in environmental legislation, especially to regulate the asset verification mechanism.